Moral education for women in the pastoral and Pythagorean letters : philosophers of the household - Huizenga, Annette Bourland. (Novum Testamentum, Supplements, 2013)
In Moral Education for Women in the Pastoral and Pythagorean Letters: Philosophers of the Household , Annette Bourland Huizenga examines the Greco-Roman moral-philosophical "curriculum" for women by comparing these two pseudepigraphic epistolary collections. The analysis is organized around four elements: textual resources, teachers and learners, instructional strategies, and subject matter. Huizenga shows that the author of the Pastorals has adopted nearly all of the "pagan" aspects of this curriculum, but has supplemented these with theological justifications drawn from Pauline literature and traditions. The letters attributed to female Pythagoreans have long been suggested as comparanda for the Pastorals, but are not well-known as sources. This volume provides a Greek edition, a new English translation, and a text history of these letters.